EPTFE‐TIPS vs repetitive LVP plus albumin for the treatment of refractory ascites in patients with cirrhosis. (15th January 2018) - Bucsics, Theresa; Hoffman, Sophie; Grünberger, Johanna; Schoder, Maria; Matzek, Wolfgang; Stadlmann, Alexander; Mandorfer, Mattias; Schwabl, Philipp; Ferlitsch, Arnulf; Peck‐Radosavljevic, Markus; Trauner, Michael; Karner, Josef; et al.
Abstract: Background & Aims: Reduction in portal pressure by self‐expandable polytetrafluoroethylene (ePTFE)‐covered transjugular intrahepatic portosystemic shunts (TIPS) is a treatment option for refractory ascites. Data on clinical outcomes after ePTFE‐TIPS vs repetitive large‐volume paracentesis (LVP) plus albumin (A) administration for the treatment of patients with refractory ascites are limited. Methods: Retrospective comparison of ePTFE‐TIPS vs LVP+A in terms of (i) control of ascites, (ii) occurrence of overt hepatic encephalopathy (HE) and (iii) transplant‐free survival in cirrhotic patients with refractory ascites. Results: Among n = 221 patients with cirrhosis and refractory ascites, n = 140 received ePTFE‐TIPS and were compared to n = 71 patients undergoing repetitive LVP+A. After ePTFE‐TIPS, ascites was controlled without any further need for paracentesis in n = 76 (54%; n = 7 without and n = 69 with diuretics). The need for frequent large‐volume paracentesis was significantly higher in the LVP+A group than with ePTFE‐TIPS (median 0.67 (IQR: 0.23‐2.63) months vs 49.5 (IQR: 5.07‐102.60) months until paracentesis, log‐rank P < .001). De‐novo incidence of HE was similar in ePTFE‐TIPS and LVP+A patients (log‐rank P = .361). Implantation of ePTFE‐TIPS was associated with improved 1‐year survival as compared to LVP+A (65.6% vs 48.4%, log‐rank P = .033). Age (odds ratio (OR):1.05; 95% confidence interval (95% CI):1.03‐1.07; P < .001), serum albumin (OR: 0.95; 95% CI: 0.92‐0.99; P = .013) and hepatocellular carcinoma (OR: 1.66; 95% CI: 1.06‐2.58; P = .026) emerged as independent predictors of survival. Conclusions: ePTFE‐TIPS results in superior control of ascites without increasing the risk for overt HE as compared to LVP+A. Although ePTFE‐TIPS improved 1‐year survival in cirrhotic patients with refractory ascites, its use was not independently associated with transplant‐free survival.